2017
DOI: 10.1080/17453674.2017.1404791
|View full text |Cite
|
Sign up to set email alerts
|

High and rising burden of hip and knee osteoarthritis in the Nordic region, 1990–2015

Abstract: Background and purposeOsteoarthritis (OA) imposes a substantial burden on individuals and societies. We report on the burden of knee and hip OA in the Nordic region.Patients and methodsWe used the findings from the 2015 Global Burden of Diseases Study to explore prevalence, years lived with disability (YLDs), and disability-adjusted life-years (DALYs) of OA in the 6 Nordic countries during 1990–2015 (population of about 27 million in 2015).ResultsDuring 1990–2015, the number of prevalent OA cases increased by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 26 publications
1
48
0
2
Order By: Relevance
“…Dabei spielen die Steigerung der Bevölkerungszah len, das zunehmende Alter und die Fettleibigkeitsepidemie eine Rolle. Insbesondere in der Zukunft ist mit weiter steigenden Zahlen von Arthrosepatienten zu rechnen [2].…”
Section: Einleitung Und Definition Der Arthroseunclassified
“…Dabei spielen die Steigerung der Bevölkerungszah len, das zunehmende Alter und die Fettleibigkeitsepidemie eine Rolle. Insbesondere in der Zukunft ist mit weiter steigenden Zahlen von Arthrosepatienten zu rechnen [2].…”
Section: Einleitung Und Definition Der Arthroseunclassified
“…Osteoarthritis (OA) of the knee is common [1], debilitating [2] and increasing in its prevalence [1]. Any therapeutic intervention that can relieve symptoms of OA, prevent its progression and/or delay the need for surgery therefore has potential to dramatically improve quality of life for patients.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis-related groups (DRGs) based payment is increasingly used in China to control hospital costs but the standards of evaluations vary. Previous review suggested that a substantial rise in the burden of osteoarthritis (OA) is expected and should be addressed in health policies and DRGs payment had potential cost-saving implications by lowering LOS [4,5]. Extended LOS remains a paramount unsolved problem and how these different factors contribute to prolonging LOS is poorly characterized [6].…”
Section: Introductionmentioning
confidence: 99%